Recreating historical Malay architecture with BIM process - Mustafa, Muhammad Hadi; Ali, Maisarah; Hashim, Khairusy Syakirin Has-Yun; Mohamad Suhaimi, Mohamad Saifulnizam (Penerbit UTM Press, Universiti Teknologi Malaysia, 2020)
In South-East Asia, the Malay architecture is among the popular subject of research because of its historical importance within the region, apart from many others. To some researchers, the Malay architecture is unique because of its intangible meaning and historically rich design characters. It is difficult to be reproduced, and only limited numbers of people are acknowledged as experts. With the introduction of technology such as BIM, it is hypothesized that the gap can be minimized. The idea of this paper is to outline the process of recreating cultural architectural design using a modern process such as Building Information Modelling (BIM) platform in specific, from data collection using Terrestrial Laser Scanning (TLS) and digitalization process in Revit software. This paper employs observation approach using data from laser scanner collected from case study and content analysis technique. While normally most of the cultural architecture is undocumented, the findings of this activity are aimed to provide guideline to develop geometrical information for heritage-enthusiast in practicing their undertakings. It is hoped that more historical and cultural architecture can be recreated and appreciated for the use and inspiration of current construction industry.